2009
DOI: 10.1080/19346182.2009.9648494
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis in freestyle snowboarding: Application of a full‐body inertial measurement system and a bilateral insole measurement system

Abstract: 2009) Biomechanical analysis in freestyle snowboarding: Application of a full-body inertial measurement system and a bilateral insole measurement system, Sports Technology, 2:1-2, 17-23To link to this article: http://dx.Several investigations show that 5-28% of all snowboarding injuries relate to the ankle joint complex. To reduce the risk of ankle injuries, the development of enhanced snowboard equipment is considered. Therefore, it is essential to understand the biomechanics in snowboarding. Scientific studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 13 publications
0
39
0
1
Order By: Relevance
“…A 2006 study used four high-speed cameras for video data collection and a force plate mounted on the snowboard to record the force during jump landings, and concluded that this method had potential for future biomechanical analyses 75. Another such study used full-body inertial and insole measurement systems 76. The inertial suit is an alternative to the traditional motion capture, which has high accuracy but is difficult to carry out in an outdoor environment, especially in the snow.…”
Section: Methodsmentioning
confidence: 99%
“…A 2006 study used four high-speed cameras for video data collection and a force plate mounted on the snowboard to record the force during jump landings, and concluded that this method had potential for future biomechanical analyses 75. Another such study used full-body inertial and insole measurement systems 76. The inertial suit is an alternative to the traditional motion capture, which has high accuracy but is difficult to carry out in an outdoor environment, especially in the snow.…”
Section: Methodsmentioning
confidence: 99%
“…Supej [3] has presented a novel system involving a GNSS RTK that returns a reference trajectory through the use of a suit, embedded with inertial sensors, to reveal subject segment motion. Kruger [4] has covered application of an inertial measurement suit in combination with a bilateral insole measurement system in freestyle snowboarding for data collection in a real snowboarding environment. Brodie [5] has used a fusion motion capture to capture 3D kinetics and kinematics of alpine ski racing.…”
Section: Introductionmentioning
confidence: 99%
“…These are becoming common in biomechanics research [22,23] and in performance assessment [24]. IMUs are small electronic devices that usually contain gyroscopes, magnetometers and accelerometers that can be fixed onto an object or onto an athlete's limb segments.…”
Section: Manual and Automated Digitisingmentioning
confidence: 99%